2022
DOI: 10.1186/s13024-022-00535-x
|View full text |Cite
|
Sign up to set email alerts
|

BIN1 is a key regulator of proinflammatory and neurodegeneration-related activation in microglia

Abstract: Background The BIN1 locus contains the second-most significant genetic risk factor for late-onset Alzheimer’s disease. BIN1 undergoes alternate splicing to generate tissue- and cell-type-specific BIN1 isoforms, which regulate membrane dynamics in a range of crucial cellular processes. Whilst the expression of BIN1 in the brain has been characterized in neurons and oligodendrocytes in detail, information regarding microglial BIN1 expression is mainly limited to large-scale transcriptomic and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 100 publications
(129 reference statements)
2
44
0
Order By: Relevance
“…For this reason it is sometimes known as “housekeeping cells” [ 1 ]. However, it has been proven that role of microglia exceeds beyond housekeeping, as it participates in the brain development, neuromodulation, synaptic plasticity, and it contributes to learning and memory processing [ 2 , 3 ]. Another group of CNS cells that possess immunological properties are astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason it is sometimes known as “housekeeping cells” [ 1 ]. However, it has been proven that role of microglia exceeds beyond housekeeping, as it participates in the brain development, neuromodulation, synaptic plasticity, and it contributes to learning and memory processing [ 2 , 3 ]. Another group of CNS cells that possess immunological properties are astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…IRF1 plays an essential role in the immune response, anti-viral mechanisms, macrophage polarization, and microglial activation [29][30][31] . Interestingly, IRF1 is regulated by BIN, the second most common risk factor for AD, and has essential roles in regulating brain in ammatory response and microglial function 32,33 . TGFI2 is associated with neuronal apoptosis, neocortical development, neurogenesis, brain defects, and mental retardation 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, BIN1 is a key regulator of microglia activation and the proinflammatory response. In vitro and in vivo studies involving silencing Bin1 expression in primary mouse microglia found that BIN1 regulated the activation of proinflammatory responses upstream of Apoe, Trem2, and Tyrobp (encoding TYRO protein tyrosine kinase binding protein), and upstream of Pu.1 (encoding Spi-1 proto-oncogene) and Irf1 (encoding interferon regulatory factor 1), which mediated the transition to DAM [ 78 ]. Conditional knockout of microglial Bin1 mitigated LPS‑mediated proinflammatory activation and the DAM gene expression profile in mice.…”
Section: Clues To the Pathogenesis Of Ad Based On “Omics” Analysis Re...mentioning
confidence: 99%
“…Conditional knockout of microglial Bin1 mitigated LPS‑mediated proinflammatory activation and the DAM gene expression profile in mice. BIN1 was also found to regulate inflammation-induced expression of Ifitm3 [ 78 ], an interferon-response gene encoding interferon induced transmembrane protein 3, which plays a role in microglial inflammatory responses to AD pathology [ 79 ]. LPS-induced upregulation of Ifitm3 was significantly impaired in the absence of Bin1 expression [ 78 ].…”
Section: Clues To the Pathogenesis Of Ad Based On “Omics” Analysis Re...mentioning
confidence: 99%
See 1 more Smart Citation